Labor trafficking in marijuana production: a hidden epidemic in the shadows of the cannabis industry - Prakash, Jaya; Erickson, Timothy B.; MacGibbon, Marti; Stoklosa, Hanni (Frontiers in Sociology, 2023)
Labor trafficking in marijuana production remains a concealed epidemic within the expanding national cannabis industry. This abstract brings attention to the systemic exploitation of vulnerable individuals engaged in cultivating, harvesting, and processing marijuana. It explores the factors contributing to labor trafficking, including demand for cheap labor, inadequate regulation, and the vulnerability of the workforce. By compiling published cases, both in peerreviewed literature and the media, this perspective investigates the extent of health issues experienced by labor-trafficked victims. These include chronic pain from repetitive tasks, respiratory problems due to exposure to pesticides and other toxic substances, musculoskeletal injuries, malnutrition, and mental health disorders stemming from trauma and extreme stress. Additionally, this perspective examines the factors contributing to the poor health outcomes of labor-trafficked victims, including hazardous working conditions, lack of access to healthcare, and physical and psychological abuse. Addressing the health challenges faced by labor-trafficked victims in the cannabis industry requires multidimensional solutions: awareness among healthcare providers, comprehensive medical services, and mental health support. Furthermore, collaborative efforts among government agencies, healthcare providers, labor organizations, and the cannabis industry are essential in addressing the health disparities faced by labor-trafficked victims.